2010
DOI: 10.1177/1557085110387788
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female Juvenile Homicide Offenders: An Empirical Analysis of U.S. Arrests by Offender Age

Abstract: Almost all of the clinical and empirical literature on female parricide victims focuses on mothers killed, with only little information available on stepmothers murdered. This study is the first to compare the victim, offender, and case correlates in incidents when mothers and stepmothers were killed. Supplementary Homicide Report Data for 1976-2007 were used to investigate similarities and differences between the two female victim types in the United States. Similarities between stepmothers and mothers includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 76 publications
(99 reference statements)
2
28
0
Order By: Relevance
“…Moreover, girls and boys in the present sample did not differ in their preference for committing accomplice-assisted homicide. it is important to note that, although our sample of girl offenders was small, the sample is proportional to the Statistics Canada 10-year average for 1997 to 2006 (li, 2008) and to supplementary homicide research data in the united States for homicides occurring between 1976 and 2007 (Heide et al, 2011). in addition, our results mirror that of roe-Sepowitz (2009), who demonstrated that two thirds of homicides perpetrated by american girls occurred concurrent to another crime.…”
Section: Ethnicitysupporting
confidence: 83%
“…Moreover, girls and boys in the present sample did not differ in their preference for committing accomplice-assisted homicide. it is important to note that, although our sample of girl offenders was small, the sample is proportional to the Statistics Canada 10-year average for 1997 to 2006 (li, 2008) and to supplementary homicide research data in the united States for homicides occurring between 1976 and 2007 (Heide et al, 2011). in addition, our results mirror that of roe-Sepowitz (2009), who demonstrated that two thirds of homicides perpetrated by american girls occurred concurrent to another crime.…”
Section: Ethnicitysupporting
confidence: 83%
“…For example, to what degree do other factors, such as intelligence, personality, psychopathy, and sexual sadism, play a role in weapon choice and victim–offender relationship? Given that juvenile homicide offenders are more likely than adults to kill in groups (10), further research might examine single offender versus multiple offender sexual homicides. Additionally, future studies might investigate whether gang involvement is a possible dynamic in sexual homicide when committed by juvenile SHOs.…”
Section: Discussionmentioning
confidence: 99%
“…This study, unlike the others using SHR data, analyzes single-victim cases. Analyses of SHR data are best suited for single-victim cases (see [10]). In addition to methodological issues, there is some evidence to suggest that the psychological makeup of single-victim SHOs may differ from those who sexually murdered more than one victim (11).…”
mentioning
confidence: 99%
“…Several national studies have used Supplementary Homicide Report data to examine differences between male and female JHOs. During the last 25 years, seven studies have investigated gender differences between juveniles aged 6 or 7 through 17 (Heide, Solomon, Sellers, & Chan, ; Heide et al, ; Loper & Cornell, ; Rowley, Ewing, & Singer, ; Sellers & Heide, ; Snyder & Sickmund, , ). In recognition of developmental differences between younger and older youths, one study explored gender differences between JHOs aged 6–12 (younger JHOs) and JHOs aged 13–17 (older JHOs) (Heide et al, ).…”
mentioning
confidence: 99%
“…Child development experts have long recognized that fundamental differences exist between younger school‐age children (ages 6–12) and older schoolchildren (13–17 years old) (Erikson, ; Heide, Solomon, Sellers, & Chan, ; Hess, Magnuson, & Beeler, ; Piaget & Inhelder, ). Youths aged 12 and younger are sometimes referred to in the professional literature as children , preadolescents , or preteens to distinguish them from adolescents or teenagers (see, e.g., Sellers & Heide, ; Shumaker and McKee, ; Shumaker & Prinz, ).…”
mentioning
confidence: 99%